Capturing Lifestyle Shopping Experience, Customer Reward, Customer Engagement, Customer Satisfaction and Online Repurchase Intention - Dewi, Ni Putu Tara Damayanti; Darma, Gede Sri (Quantitative Economics and Management Studies, 2024)
This study is aimed at analyzing the influence of lifestyle shopping experience, customer rewards, customer engagement on repurchase intention, and the role of customer satisfaction as a mediator. This study was carried out at Beachwalk Bali which launched an online shopping website called Mall to Go (https://malltogo.izy.ai/). Then, this study was carried out using a quantitative approach. The target population for this study is consumers who have shopped at Beachwalk Bali using the Mall to Go Beachwalk Bali application more than twice in 1 month. Through purposive sampling, a sample of 200 respondents was obtained. Next, data was collected through a questionnaire with a 5 Likert scale, which was then analyzed using SEM-PLS. From the results, it can be seen that there is a positive and significant relationship between lifestyle shopping experience, customer reward, customer engagement on repurchase intention, and customer satisfaction. Not only that, customer satisfaction is also proven to have a role in mediating the influence between customer reward and customer engagement on online repurchase intention. However, customer satisfaction fails to mediate the influence between lifestyle shopping experiences and online repurchase intention. Further suggestions to the management of Beachwalk Bali and future researchers have been presented in this study.